1997
DOI: 10.1210/en.138.1.254
|View full text |Cite
|
Sign up to set email alerts
|

Rainbow Trout Liver Expresses Two Iodothyronine Phenolic Ring Deiodinase Pathways with the Characteristics of Mammalian Types I and II 5'-Deiodinases

Abstract: Deiodinases are major determinants of thyroid hormone tissue availability and disposal. The knowledge of the expression of these enzymes in lower species is important to understand evolutionary and ontogenetic aspects of thyroid hormone action and metabolism. Here we have studied outer ring deiodination in the trout liver using both reverse T 3 (rT 3 ) and T 4 as substrates. The use of rT 3 disclosed two enzymatic components with the characteristics of mammalian types I and II 5Ј-deiodinases. The high rT 3 -K … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…Fenton et al (27) have measured DI activity in rainbow trout tissues, including the skin. Other studies have also measured DI activity in rainbow trout brain, liver, and gonads (28)(29)(30)(31)(32). Sweeting and Eales (33) conducted several experiments with rainbow trout liver microsomes and determined that outer ring deiodination of thyroxine (T4) was the dominant thyroid hormone process in these cell fractions.…”
Section: Resultsmentioning
confidence: 99%
“…Fenton et al (27) have measured DI activity in rainbow trout tissues, including the skin. Other studies have also measured DI activity in rainbow trout brain, liver, and gonads (28)(29)(30)(31)(32). Sweeting and Eales (33) conducted several experiments with rainbow trout liver microsomes and determined that outer ring deiodination of thyroxine (T4) was the dominant thyroid hormone process in these cell fractions.…”
Section: Resultsmentioning
confidence: 99%
“…DIs), and specifically to prevent disulfide bonds from forming between active sites in selenocysteine residues. DTT is generally regarded as an essential thiol co-factor for investigating DI activity in in vitro assay systems 30a, 34. Specifically, studies examining DI activity in fish hepatic microsomes have found that DTT is required to maintain DI activity and that increasing the amount of DTT can often increase the level of DI activity 30a, 34.…”
Section: Discussionmentioning
confidence: 99%
“…The difficulty in identifying amphibian D1 activity resulted from the biochemical properties of the enzyme. Indeed, a critically important characteristic of D1-catalyzed deiodination is its remarkable sensitivity to inhibition by 6-n-propyl-2-thiouracil (PTU), with the exception of fish (Orozco et al 1997, Sanders et al 1997) and amphibian D1 , which are less sensitive to this inhibitor. In fact, PTU sensitivity has been used to demonstrate the specificity of T 4 to T 3 conversion and to distinguish D1 from the other Ds.…”
Section: Biochemical Propertiesmentioning
confidence: 99%